Mercury and Methylmercury Toxicology and Risk Assessment - Chan, Laurie Hing Man (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Mercury is a global pollutant that affects the health of both humans and ecosystems. This Special Issue collects three review papers and six research articles that report on the latest findings on the mechanisms of mercury toxicology and its impacts on environmental health. This collection of papers provides useful, new information on the mechanisms of mercury toxicity and methods of improving the risk assessment of mercury exposure.